Effect of Dialectic Behavior Therapy on Self-conscious Emotions and Family Quality of Life in Mothers of Children with Intellectual Disability - Karim Aali Sari Nasirlo; Farah Naderi; Rezvan Homaei; Behnam Makvandi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims having children with intellectual disability can cause psychological, emotional and social problems for the parents, especially mothers. The present study aims to examine the effect of dialectic behavior therapy (DBT) on self-conscious emotions and family quality of life (QoL) in mothers of children with intellectual disability.Methods This is a quasi-experimental study with a pre-test/post-test/ follow-up design. The study population consists of all mothers of children with intellectual disability in Ardebil, Iran in 2021. Of these, 37 were selected using a purposive sampling method and randomly divided into intervention and control groups. The mothers in the intervention group received eight sessions of DBT for two months. Tangney et al.'s test of self-conscious affect and the beach center family QoL scale were used in this study. The data were analyzed using mixed ANOVA.Results The DBT had a significant effect on positive self-conscious affect (F=75.20; Eta squared=0.68; P=0001), negative self-conscious affect (F=45.19; Eta squared =0.56; P=0001) and family QoL (F=71.74; Eta squared=0.67; P=0001) in mothers.Conclusion The DBT can improve self-conscious emotions and family QoL in mothers of children with intellectual disability by employing techniques such as distress tolerance, mindfulness, and emotional regulation.